Qualitative and quantitative HPLC-ELSD-ESI-MS analysis of steroidal saponins in fenugreek seed - Król-Kogus Barbara; Głód Daniel; Krauze-Baranowska Mirosława (Acta Pharmaceutica)
Fenugreek seeds are known as a source of various compounds, the most common of which are steroidal saponins. However, despite the growing interest in this plant material as a healing agent, spice and dietary supplement ingredient, the composition of Polish fenugreek seeds remains unknown. Therefore, the steroidal saponin complex in the seeds of T. foenum-graecum cultivated in Poland was qualitatively and quantitatively analyzed by the HPLC-ELSDESI-MS method. Two C-18 columns connected in series were used for the first time in analysis of fenugreek saponins and ELS detector parameters were optimized. A total of 26 furostanol saponins were revealed, of which 24 were tentatively identified. The HPLC-ELSD method developed for quantitative analysis was preliminarily validated and the determined amount of steroidal saponins in Polish fenugreek seeds was 0.14 %.